2020
DOI: 10.1088/1742-6596/1491/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Project Based Laboratory Learning to Increase Student’s Science Process Skills and Creativity

Abstract: The Project Based Laboratory Learning (PJBLL) model is an innovative physics teaching model designed to enhance student’s sciences process skills and creativity. Therefore, this research aims to analyze the effectiveness of PJBLL model to improve sciences process skills and creativity physics students who were programmers in Unesa’s laboratory. The study design used one-group pretest-posttest design. Data collection methods were conducted by using tests sciences process skills and creativity. Data is analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Minister of Education and Culture No. 73 of 2013 concerning that the Indonesian national qualification framework curriculum in the field of higher education requires universities to compile a curriculum so that students have superior competencies with various skills that are in line with the demands of the 21st century, including scientific creativity, critical thinking skills, collaborative skills, literacy, skills to utilize ICT, and problem-solving skills (Ministry of Education and Culture, 2013;Jatmiko et al, 2018;Suyidno et al, 2018;Suyidno et al, 2019;Dwikoranto et al, 2020).…”
Section: |260mentioning
confidence: 99%
“…Minister of Education and Culture No. 73 of 2013 concerning that the Indonesian national qualification framework curriculum in the field of higher education requires universities to compile a curriculum so that students have superior competencies with various skills that are in line with the demands of the 21st century, including scientific creativity, critical thinking skills, collaborative skills, literacy, skills to utilize ICT, and problem-solving skills (Ministry of Education and Culture, 2013;Jatmiko et al, 2018;Suyidno et al, 2018;Suyidno et al, 2019;Dwikoranto et al, 2020).…”
Section: |260mentioning
confidence: 99%
“…Research shows that Indonesian students have low creativity [8,9,10] due to the learning process that cannot accommodate students' creativity. It is also demonstrated that the teachers have not optimized pedagogical strategies in the classroom [11].…”
Section: Introductionmentioning
confidence: 99%
“…Project-Based Learning was studied by Shafaei and Rahim (2015), Munezero and Bekuta (2016), Filho, Shiel, and Paço (2016), and Dwikoranto et al (2019). In these works, one can see the methodological task of education through project activities.…”
Section: Introductionmentioning
confidence: 99%
“…While the initial courses often use explanatory, visual, and problem-based methods, the senior courses use semi-exploratory and research methods that give them a direction to choose their capabilities. For example, the semi-search method provides an opportunity for pupils to work independently, as a result of developing the skills of drawing up a research plan, conducting observations, and so on (Dwikoranto et al, 2019;Stentoft, 2019;Mayolo-Deloisa, Ramos-de-la-Peña, & Aguilar, 2019).…”
mentioning
confidence: 99%